Pelatihan Penanganan Korban: Healthy, Hydrated, and Optimal Safety During School Festival - Darmareja, Rycco; Izza, Nurul; Pamungkas, Wahyu Putri; Pangestu, Siti Yaasinta Dwi; Almira, Dinda Marsha; Alettha, Keyza Zie; Priwardani, Khaerunisa (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: School festivals are used as positive activities to develop interests, talents, and creativity as well as a way to implement innovative learning. Festival activities often cause crowds of people and result in health problems such as fainting, dehydration, physical injury, and even death due to crowding. The committee is responsible for organizing the festival from preparation to completion of activities. Aim: The training was carried out to increase the competence of the school festival committee in carrying out first aid for victims with health problems arising from festival crowds. Method: The method used is training, including providing education and demonstration activities related to the management of helping victims caused by crowds during school festivals. The target of the program is the Depok High School Hyperduty festival committee of 24 people. As an evaluation, data was collected using a questionnaire with pre-and post-test methods as well as observation sheets according to standard aid measures and then analyzed. Result: Data analysis shows that there was an increase in knowledge of 37.5% and attitude of 8.3% after the program was carried out with a significance value of p 0.001 for knowledge and 0.011 for the attitude variable. Apart from that, the skills in providing first aid to victims of cardiac arrest during school festivals are in the range of good to good. Conclusion: There is a significant influence of training on increasing participants' knowledge, attitudes, and skills in festival management.